PENGARUH EDUKASI GIZI TERHADAP PENGETAHUAN DAN PRAKTIK CALON IBU DALAM PENCEGAHAN KURANG ENERGI KRONIK IBU HAMIL (Studi pada Pengantin Baru Wanita di Wilayah Kerja Puskesmas Duren, Bandungan, Semarang) - Fifiantyas Amalia; Sri Achadi Nugraheni; Apoina Kartini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Chronic Energy Deficiency is a condition caused by an imbalance between intake and energy and protein needs. The impact of CED is low birth weight (LBW), congenital defects and neonatal mortality. The purpose of this study is to determine the effect of nutrition education on knowledge and practice of prospective mothers related to prevention of pregnant women’s CED. This research used Quasi-Experimental method by using one-group pre-test - post-test design. The samples were 38 newlywed women taken by purposive sampling technique. The normality test used Shapiro Wilk. Data analysis used was Wilcoxon Signed Ranks Test and Chi-Square. The results showed an increase in the knowledge of good categories as much as 55.2%. In practice, there was a decrease in good practice category by 13.2%. The results of Wilcoxon test found that there was a difference between the knowledge before and after nutrition education with p-value = 0.001 (p <0.005) and there was a difference between practice before and after nutrition education with p-value = 0.003 (p <0.005). The results of chi square test found that there was no correlation between educational background with knowledge p-value = 0.089 (p> 0.005), there was no relationship between educational background and practice p-value = 0.393 (p> 0.005), there was no relationship between work background and knowledge value = 0.636 (p> 0.005), there is a relationship between work background and practice p-value = 0.029 (p <0.005). It can be concluded that there is an effect of nutrition education on improving knowledge of CED prevention but there is no effect of nutrition education on improving prevention practice of CED. The suggestion of this research is that the newlyweds woman do prevention of CED in the form of routine meals three times a day and maintain their diet.